Perlindungan Hukum Bagi Tenaga Kerja Indonesia Di Luar Negeri (Lex Jurnalica, 2012)
AbstractMany plight of migrant workers abroad, such as assault, rape, suicide, until not given wages for work. Many who view this problem due to the low level of education of migrant workers. But in addition to this, the lack of an integrated protection system of the country, both sending and destination countries, also contributed to the above facts. System protection for workers has yet to recognize the foreign workforce who work in the informal sector, both nationally and internationally. Law enforcement approach to the regulation of migration in destination countries tend to put undocumented migrant workers at a disadvantage, because they generally have to bear the consequences are less subjected to inhuman treatment and is often referred to as illegal. Issues that will be addressed in this study is